Pathophysiological Mechanisms of Premature Ventricular Complexes - Hoogendijk, Mark G.; Géczy, Tamás; Yap, Sing-Chien; Szili-Torok, Tamas (Frontiers in Physiology, 2020)
Premature ventricular complexes (PVCs) are the most common ventricular arrhythmia. Despite the high prevalence, the cause of PVCs remains elusive in most patients. A better understanding of the underlying pathophysiological mechanism may help to steer future research. This review aims to provide an overview of the potential pathophysiological mechanisms of PVCs and their differentiation.